The University of the Philippines, 1908-1986 as seen through the presidential papers - Sarmiento, Candida G.; Medina, Isagani R.; Granda, Yolanda C. (Quezon City Institute of Library Science, University of the Philippines Diliman, 1993)
This is a historical study which presents a narrative record of each University President's contribution to the historical development of the University of the Philippines from 1908-1986. The study deals on the more important pronouncements of the President of the University, highlights of events that happened during the term of administration.
The paper aims to familiarize future generations of alumni with significant development in the University. This study will be useful for scholars, the students of history and of education, as well as the general citizens who wants to know more about the University of the Philippines. It also includes biographies of the fourteen university presidents from President Murray S. Bartlett to Edgardo J. Angara. A guide to the presidential papers available at the University Archives and Records Depository and a list of Colleges, Schools, Institutions and Centers of the University of the Philippines showing its founding dates are included in the paper.
Typescript.
Vita.
Special Problem (Master of Library Science)
Keywords: College presidents -- Philippines -- Quezon City; University of the Philippines -- Presidents -- Administration; University of the Philippines -- Presidents -- History; University presidents See College presidents